Information needs and use of distance education students of College Assurance Plan (CAP) Distance Education (DE) Program - Lomerio, Reina R. (2007)
Distance education is becoming an important educational concept and practice nowadays. This form of education serves as an alternative form of education to students with "special" cases and reasons for not being able to attend regular schooling. This study aimed to determine these students' needs, specifically the CAP College Foundation, Inc. Distance Education Program students' current and prospective information needs and use in terms of the content and format. It also revealed the DE students' perception and personal assessment of the usage, role and relevance of their own host university library and its information delivery programs (CAP College Library) or any other library in their information research and retrieval.